Ne bis in idem as a blurred principle in national criminal case law - Melgar Cucho, Jorge Luis (2022)
Upon analyzing the diversity and multiple number of punitive procedures and processes existing in Peru, in the not so hypothetical case that a case or fact has been aired, administratively at first, concluding in a disciplinary sanction and, in the private jurisdiction (military) subsequently, and consequently in the ordinary or common jurisdiction, in view of the existence of procedural accusatory mechanisms, it is possible for a person who committed an offense to be punished and for the same fact to be subject to an administrative disciplinary process and other proceedings of a restrictive criminal and ordinary criminal nature. In this scenario, the ne bis in idem principle is a basic guarantee in every punitive proceeding and that only admits one possibility of a second process, through the review of a judgment, since the purpose of said process is to preserve the need to consolidate a right and the principles such as the one being investigated, to avoid any injustice. Hence, this principle seeks to make sure that a State governed by the rule of law dispel uncertainty and to maintain a legal security and respect for the citizen and his dignity as a fundamental basis of the State itself and its social organization.